The Effectiveness of Online Learning in Material Learning Systems of Linear Equations of Two Variables - Muhammad S. Makalalg; Victor R. Sulangi; Anetha L. F. Tilaar (Departement of Mathematics Education, 2023)
The purpose of this study is to determine the efficacy of learning from learning material on a system of two-variable linear equations (SPLDV) based on the learning outcomes of students at SMP Negeri 2 Kotamobagu. This research is descriptive in nature and employs a quantitative methodology. The participants in this research were Mathematics teachers and seventh-grade students at SMP Negeri 2 Kotamobagu for the academic year 2021/22. The purpose of this study is to determine the efficacy of risky learning on the mathematics topic of the two-variable linear equations (SPLDV) system. This research's data acquisition occurred in March 2021. Data on student learning outcomes and teacher and student responses to the implementation of courageous learning were included in this study. This study's data were collected via written examinations, questionnaires, and interviews. 1) the effectiveness of learning mathematics subject material on a system of two-variable linear equations (SPLDV) in terms of effective student learning outcomes and included in the very high effectiveness criteria with a percentage of 95%; 2) student responses to courageous learning of the mathematics subject system of two-variable linear equations (SPLDV) are excellent or practical with a percentage of 100% as well as responses from teachees.Effectiveness of courageous learning in mathematics